Effects of the growth temperature on the properties of spray deposited CuInS2 thin films for photovoltaic applications. Issue 3 (April 2015) - Baneto, Mazabalo; Enesca, Alexandru; Mihoreanu, Ciprian; Lare, Yendoubé; Jondo, Koffi; Napo, Kossi; Duta, Anca
Abstract: CuInS2 absorber thin films were prepared by spray pyrolysis deposition at different substrate temperatures (250 °C, 300 °C and 350 °C) using an aqueous solution of CuCl2, InCl3 and SC(NH2 )2 at a precursor molar ratio of Cu:In:S=1:1.25:4.5. The effect of the substrate׳s temperature on the structural, morphological, optical and electrical properties of CuInS2 thin films was investigated. The X-ray diffraction patterns showed that CuInS2 has a tetragonal structure. The results show that the films deposited at 300 °C have improved electrical conduction and photocurrent values. When increasing the substrate׳s temperature the absorbance decreases while the band gap energy increases, as a combined effect of crystallinity, morphology and deviation from stoichiometry.